Ascorbic acid content in apple pulp, peel, and monovarietal cloudy juices of 64 different cultivars. (31st December 2017) - Bassi, Michele; Lubes, Giuseppe; Bianchi, Flavia; Agnolet, Sara; Ciesa, Flavio; Brunner, Karin; Guerra, Walter; Robatscher, Peter; Oberhuber, Michael
ABSTRACT: The present work was designed to compare the vitamin C (ascorbic acid, AsA) content of pulp, peel, and juice of 64 apple cultivars. These cultivars were carefully identified as 'true to type' by molecular genetic tools, grown in the same site under identical conditions and processed by a standardized protocol. Twenty-one of them, accounting for more than 95% of the apple production of South Tyrol, were chosen to represent the current market, 16 were old or local cultivars formerly grown in the area, and 27 were new cultivars, including 15 with scab resistance and 12 with red flesh fruit. For the determination of the AsA content, a new High-Performance Liquid Chromatography with Diode-Array Detection method was developed and validated. While old cultivars stood out for their high AsA content in pulp and peel, the red-fleshed cultivars are the ones maintaining most of their AsA content during processing. Our data thus suggest a potential for old and red-fleshed cultivars for healthy juices or further processed food components.